Digital implant restoration and full-mouth occlusal reconstruction guided by multimode data fusion - GONG Delong; YU Yiqiang; LIU Weicai; LI Chaoyuan; SU Jiansheng (Kouqiang hemian waike zazhi)
[Objective:] To explore the feasibility of applying multimodal data fusion to guide complicated digital implant restoration and full-mouth occlusal reconstruction. [Methods:] For a patient with severely worn dentition and dentition defects, the multimodal data of her oral and maxillary system were obtained by intraoral scanning (IOS), extral-oral face scanning (EOS), cone beam computed tomography (CBCT) examination and jaw movement, which can be integrated to create a four-dimensional virtual dental patient (VDP) by fusion. Digital implant restoration and full-mouth occlusal reconstruction were conducted under the guidance of the four-dimensional VDP. The dynamic occlusal data was obtained using the optically positioned mandibular motion system, and the final restoration was designed and manufactured by computer-aided design and computer-aided manufacturing (CAD/CAM). Finally, the full-mouth occlusal reconstruction was completed and we have given an objective evaluation. [Results:] The case gets a good restoration effect. The patient is satisfied with aesthetics and functionality of full-mouth occlusal reconstruction, with her oral and jaw system healthy and comfortable. As the objective evaluation showed, both static occlusion in intercuspal position (ICP) and dynamic occlusion during forward movement and lateral movement had been significantly improved, and satisfactory therapeutic results had been achieved in both the aesthetic area of the anterior teeth and the functional area of the posterior teeth. [Conclusion:] It is feasible to conduct complicated digital implant restoration and full-mouth occlusal reconstruction guided by multimode data fusion, which is worth promoting.